Clinical Utility of Preoperative Computed Tomography in Patients With Endometrial Cancer. Issue 8 (1st October 2017) - Bogani, Giorgio; Gostout, Bobbie S.; Dowdy, Sean C.; Multinu, Francesco; Casarin, Jvan; Cliby, William A.; Frigerio, Luigi; Kim, Bohyun; Weaver, Amy L.; Glaser, Gretchen E.; Mariani, Andrea
Abstract : Objective: The aim of this study was to determine the clinical utility of routine preoperative pelvic and abdominal computed tomography (CT) examinations in patients with endometrial cancer (EC). Methods: We retrospectively reviewed records from patients with EC who underwent a preoperative endometrial biopsy and had surgery at our institution from January 1999 through December 2008. In the subset with an abdominal CT scan obtained within 3 months before surgery, we evaluated the clinical utility of the CT scan. Results: Overall, 224 patients (18%) had a preoperative endometrial biopsy and an available CT scan. Gross intra-abdominal disease was observed in 10% and 20% of patients with preoperative diagnosis of endometrioid G3 and type II EC, respectively, whereas less than 5% of patients had a preoperative diagnosis of hyperplasia or low-grade EC. When examining retroperitoneal findings, we observed that a negative CT scan of the pelvis did not exclude the presence of pelvic node metastasis. Alternately, a negative CT scan in the para-aortic area generally reduced the probability of finding para-aortic dissemination but with an overall low sensitivity (42%). However, the sensitivity for para-aortic dissemination was as high as 67% in patients with G3 endometrioid cancer. In the case of negative para-aortic nodes in the CT scan, the risk of para-aortic node metastases decreased from 18.8% to 7.5% in patients with endometrioid G3 EC. Up to 15% of patients with endometrioid G3 cancer had clinically relevant incidental findings that necessitated medical or surgical intervention. Conclusions: In patients with endometrioid G3 and type II EC diagnosed by the preoperative biopsy, CT scans may help guide the operative plan by facilitating preoperative identification of gross intra-abdominal disease and enlarged positive para-aortic nodes that are not detectable during physical examinations. In addition, CT may reveal other clinically relevant incidental findings.